2004
DOI: 10.1523/jneurosci.2106-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Expression of Acetylcholinesterase Impairs Glutamatergic Synaptogenesis in Hippocampal Neurons

Abstract: Acetylcholinesterase (AChE) exerts noncatalytic activities on neural cell differentiation, adhesion, and neuritogenesis independently of its catalytic function. The noncatalytic functions of AChE have been attributed to its peripheral anionic site (PAS)-mediated proteinprotein interactions. Structurally, AChE is highly homologous to the extracellular domain of neuroligin, a postsynaptic transmembrane molecule that interacts with presynaptic ␤-neurexins, thus facilitating synaptic formation and maturation. Pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 74 publications
1
55
0
Order By: Relevance
“…It was also surprising that CGN express such a high level of catalytic activity and protein, because CGN are primarily glutamatergic, however express cholinergic receptors, but have not previously been shown to express high levels of AChE [Schousboe et al, 1985;Fucile et al, 2004]. AChE has been shown to be involved transiently in neuritogenesis, and the CGN may represent immature neurons that express AChE prior to other more mature glutamatergic markers [Layer, 1990;Dong et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…It was also surprising that CGN express such a high level of catalytic activity and protein, because CGN are primarily glutamatergic, however express cholinergic receptors, but have not previously been shown to express high levels of AChE [Schousboe et al, 1985;Fucile et al, 2004]. AChE has been shown to be involved transiently in neuritogenesis, and the CGN may represent immature neurons that express AChE prior to other more mature glutamatergic markers [Layer, 1990;Dong et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…Primary Cell Culture Dissociated embryonic hippocampal neurons were grown as reported [14] . Neurons were treated at the 3rd or 5th day in culture (DIC), for 3 days with 3-10 M of the positively-charged PAS ligand, 1,5-bis (4-allyldimethylammoniumphenyl) pentan-3-one dibromide (BW284c51/BW, Sigma, St. Louis, Mo., USA), the active site AChE inhibitor physostigmine or the rat AChE antisense EN101 (12 g/ml) or inverse oligonucleotide INV101 (12 g/ml) together with BW [22] .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, an extracellular PAS blockade, which affects Neuroligin 1 expression, could be predicted to interfere with neuritogenesis and/or modify neuronal cytoarchitecture and synaptic activity. Indeed, our recent study found that inhibition of the peripheral site of AChE induces overexpression of this molecule accompanied by impaired glutamatergic synaptogenesis [14] .…”
mentioning
confidence: 99%
“…The major extracellular domain of neuroligins is homologous to acetylcholinesterase (AChE) but lacks cholinesterase activity and mediates binding to neurexins. Curiously, overexpression of AChE reduces levels of β-neurexins in vivo and in culture, and impairs genesis of glutamatergic synapses in culture, indicating that there is cross-talk between the two proteins [13,14]. Neuroligins form homomultimers through the AChE-homologous domain, a structural association that is important for neuroligin function [15,16].…”
Section: Structure Of Neurexins and Neuroliginsmentioning
confidence: 99%